Plastic injection molding / Hasdiana Hassan - Hassan, Hasdiana (2003)
Nowadays, manufacturing process has become the important process towards globalization of technology especially in industrial application. One of the important parts in manufacturing process is Plastic injection molding, which required producing very good product. This project describes the manufacturing process, which usually occur in any product using injection molding. Design, Injection molding process, troubleshooting and solve, types of product using this method and material will be considered in the analysis to produce the good product. Factor of safety the product also considered in this analysis. The projects will discuss fully plastic injection-molding method of process. The economical production of quality molded plastics products is a reflection of careful choice of both the plastic material and the process to produce this material in the desired shape and size. There are two types of plastic materials; thermosetting plastic, and thermoplastic plastic. Many thermosetting materials are usually molded by the action of heat and pressure in compression molds or transfer molds. On the other hand, the thermoplastic materials are generally molded by injection molding process wherein the material is heated to desired plasticity and injected into the relatively cool mold to solidify.